DETECTION OF SCANS - REDON, XAVIER; FEAUTRIER, PAUL (Parallel algorithms and applications, 2000)
Most automatic parallelizes are based on the detection of independent operations. Dependence analysis is mainly a syntactical process, in which the actual data transformations are ignored. There is another source of parallelism, which relies on semantical information, namely the detection of reductions and scans. Scans and reductions are quite frequent in scientific codes and are implemented efficiently on most parallel computers. We present here a new Scan detector which is based on the normalization of systems of recurrence equations. This allows the detection of scans in loops nests of arbitrary depth and on multi-dimensional arrays, and gives a uniform treatment for scalar reductions, array reductions, and arrays of reductions.